2014
DOI: 10.1016/j.juro.2013.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Folate Intake on Prostate Cancer Recurrence Following Definitive Therapy: Data from CaPSURE™

Abstract: Purpose A randomized, placebo controlled clinical trial of folic acid supplementation for the chemoprevention of colorectal adenoma revealed an increased incidence of prostate cancer in the treatment group. Limited data exist on postdiagnostic folate/folic acid intake and the risk of prostate cancer progression. We prospectively examined the association between postdiagnostic folate consumption and the risk of prostate cancer recurrence after radical prostatectomy, external beam radiation therapy and brachythe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In another study from the same cohort in men with M0 disease at presentation [53], total folate and dietary folate intake was not associated with PCa recurrence. However, patients with severely deficient dietary folate intake (lowest decile, range 123-252 mg) were at a 2.6-fold increase risk of PCa progression after radical prostatectomy (HR 2.56, 95% CI 1.23-5.29, p = 0.01).…”
Section: Dietary Factors and Pca Recurrence Progression And Survivalmentioning
confidence: 83%
“…In another study from the same cohort in men with M0 disease at presentation [53], total folate and dietary folate intake was not associated with PCa recurrence. However, patients with severely deficient dietary folate intake (lowest decile, range 123-252 mg) were at a 2.6-fold increase risk of PCa progression after radical prostatectomy (HR 2.56, 95% CI 1.23-5.29, p = 0.01).…”
Section: Dietary Factors and Pca Recurrence Progression And Survivalmentioning
confidence: 83%
“…There has been little research into whether folate intake in men with PCa might affect the progression of the disease, but the data available have not shown any evidence of an association of folate intake with PrCa progression [20] or survival [21]. To understand better the potential role of folate in PCa progression, more data are needed from large observational studies (or randomised trials) with long-term follow-up, circulating folate, and PCa tissue to investigate whether higher circulating concentrations are associated with quantifiable local molecular changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis reported that higher concentrations of vitamin B 12 and folate have a modest 12% increased risk of prostate cancer [155]. In people who have prostate cancer, available data do not show an effect of consumption of folate on disease progression [156] or survival [157]. In conclusion, the association of folate and vitamin B 12 with prostate cancer is unclear and requires further investigation.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%